ARD1 stabilization of TSC2 suppresses tumorigenesis through the mTOR signaling pathway - Kuo, Hsu-Ping; Lee, Dung-Fang; Chen, Chun-Te; Liu, Mo; Chou, Chao-Kai; Lee, Hong-Jen; Du, Yi; Xie, Xiaoming; Wei, Yongkun; Xia, Weiya; Weihua, Zhang; Yang, Jer-Yen; et al. (Science signaling, 2010)
Mammalian target of rapamycin (mTOR) regulates various cellular functions, including tumorigenesis, and is inhibited by the tuberous sclerosis 1 (TSC1)-TSC2 complex. Here, we demonstrate that arrest-defective protein 1 (ARD1) physically interacts with, acetylates, and stabilizes TSC2, thereby repressing mTOR activity. The inhibition of mTOR by ARD1 inhibits cell proliferation and increases autophagy, thereby inhibiting tumorigenicity. Correlation between ARD1 and TSC2 abundance was apparent in multiple tumor types. Moreover, evaluation of loss of heterozygosity at Xq28 revealed allelic loss in 31% of tested breast cancer cell lines and tumor samples. Together, our findings suggest that ARD1 functions as an inhibitor of the mTOR pathway and that dysregulation of the ARD1-TSC2-mTOR axis may contribute to cancer development.